2018
DOI: 10.1016/j.inteco.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and terror in Africa

Abstract: This study examines the role of globalization on terrorism in 51 African countries for the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 63 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…For instance, Muroi and Baumann (2009) found that wealth increases crime in low income countries, but decreases crime in high income countries. Asongu and Biekpe (2017) recently conducted a study based on 51 African countries for the period 1986-2011 which supports a relationship between globalization and terrorism. However, they call for further research to understand the dynamics of terrorism.…”
Section: Digest Of Middle East Studiesmentioning
confidence: 92%
See 1 more Smart Citation
“…For instance, Muroi and Baumann (2009) found that wealth increases crime in low income countries, but decreases crime in high income countries. Asongu and Biekpe (2017) recently conducted a study based on 51 African countries for the period 1986-2011 which supports a relationship between globalization and terrorism. However, they call for further research to understand the dynamics of terrorism.…”
Section: Digest Of Middle East Studiesmentioning
confidence: 92%
“…On the other hand, globalization and trade integration also have an impact on terrorism (Asongu & Biekpe, 2017;Daniel & Verdier, 2006). Based on 51 African countries in the period 1986 to 2011, Asongu and Biekpe (2017) found that political globalization increases both domestic and transnational terrorism, while social and general globalization increase transnational terrorism. However, economic globalization reduces domestic terrorism.…”
Section: Digest Of Middle East Studiesmentioning
confidence: 99%
“…The Boko Haram is flurishing in North Eastern Nigeria and neighbouring countries particularly in areas where government presence is weak. For example according to Asongu and Biekpe (2018) According to Solomon (2017), over the past five years, approximately 20, 000 people have been killed across Africa by two notable terrorist groups which have accounted for about 71% (91%) of terrorism incidents (fatalities). The author maintains that the number of terrorism-related deaths reached its peak in 2015 when the Boko Haram massacred more than 8,000 people in Niger, Chad, Cameroon and Nigeria.…”
Section: Stylized Factsmentioning
confidence: 99%
“…The dependent indicator is a record of yearly terrorism incidents experienced by a country. In order to correct for the positive skew in the data and avoid mathematical concerns about log-transforming zeros, the study is in accordance with the literature (Choi & Salehyan, 2013;Bandyopadhyay et al, 2014;Efobi & Asongu, 2016;Asongu & Biekpe, 2018) in adding one to the base and taking the natural logarithm of terrorism incidents.…”
Section: Datamentioning
confidence: 99%
“…The adopted elements in the conditioning information set are: internal conflicts, political globalisation, inflation, infrastructure, exchange rate and trade openness. The choice of these indicators in the conditioning information set is motivated by contemporary terrorism literature (Bandyopadhyay et al 2014, Efobi and Asongu 2016, Asongu and Biekpe 2018, Asongu and Amankwah-Amoah 2018. It is expected that trade openness, better infrastructure and improvements in exchange rate will have a positive incidence on the exports of resources (Akpan 2014, Asongu 2015a.…”
Section: Datamentioning
confidence: 99%